PENGGUNAAN ILUSTRASI SEBAGAI DAYA TARIK PADA IKLAN MEDIA CETAK - Duto Hartanto, Deddi (Institute of Research and Community Outreach - Petra Christian University, 2001)
The usage of illustration in printed advertising media is considerably important. Illustration functions only for decoration to attract attention%2C but also act as visualisation of advertising ideas. If ilustration is functioned properly%2C it would be a very effective tool for delivening advertising messages. Abstract in Bahasa Indonesia : Penggunaan ilustrasi pada iklan media cetak merupakan hal penting untuk diperhatikan. Ilustrasi bukan hanya sebagai hiasan yang menarik perhatian saja%2C tetapi sebagai visualisasi gagasan pesan iklan. Apabila tepat penggunaannya akan sangat efektif dalam menyampaikan isi pesan iklan tersebut. advertising illustration%2C printed media%2C attraction device